Comparing Methods for Pyrite Surface Area Measurement Through Optical, Aqueous, and Gaseous Approaches - Samantha Macchi; Martin Nemer; Melissa M. Mills; Melissa L. Meyerson; Hans W. Papenguth; John H. Taphouse; Noah B. Schorr (Sci)
Accurate surface area data are imperative for the development of meaningful property–function relationships. Nitrogen gas (N2) adsorption/Brunauer–Emmet–Teller (BET) surface area analysis is a widely used technique for surface area characterization of materials because of straightforward sample preparation, automation, and low cost. However, iron disulfide (FeS2) does not typically exhibit quantifiable N2 monolayer formation in BET measurements. FeS2 has been applied in fields such as batteries, catalysis, and adsorption, all of which would benefit from techniques that reliably assess surface area (SSA) of the active material. To address this, we evaluated FeS2 samples by combining alternative surface characterization techniques to quantify SSA. Ten different FeS2 samples from various manufacturers are characterized via BET, laser diffraction, scanning electron microscopy, non-contact profilometry, and liquid dye adsorption. Compared to BET, which resulted in a wide range of SSAs between 0.049–1.213 m2 g−1, liquid dye adsorption was found to be accurate for pyrite samples at low sample masses (<50 mg), with SSA values between 0.99–10.20 m2 g−1. Using an optical characterization approach, which combined particle size and surface roughness data, we readily estimated SSA of the particles and found these values correlated linearly with liquid adsorption but not BET values. This work serves to help researchers choose a more fitting method for examining low surface area materials like FeS2 and can easily be applied to other minerals for quantitative and qualitative surface area comparisons.